eDNA Metabarcoding Reveals Homogenization of Fish in Fujiang Segments Isolated by Cascading Hydroelectric Stations - Chao Deng; Shixia Huang; Bolin Chen; Rong Huang; Jiaqi Zhang; Zhihui Xiao; Chengcheng Ma; Zhijian Wang; Xiaohong Liu (Animals, 2025)
Background: The Fujiang River, a first-order branch of Jialing River, has for years been separated into six segments by six cascading hydropower stations in its downstream. However, the impact of cascading hydropower stations on its aquatic biota communities remains unclear. Methods: eDNA samples were collected in the upper, middle, and lower reaches of each river fragment during March, May, July, and December 2023, and after species identification, various statistical analyses including β-diversity, NMDS and MantelTest were performed using the R platform. Results: A total of 82 fish species belonging to 15 families were identified. The fish communities in the six fragments of the downstream Fujiang River showed a high degree of overlap, and a notable aggregation of fish communities between the upper, middle, and lower areas within each river section was also observed. Flow velocity (FV) and water temperature (TEMP) were found to be important factors in shaping fish distribution. Conclusion: Fish composition and distribution trend towards homogenization in the downstream of the Fujiang River.